(untitled) - Durke, William J (Standford, California, 1994)
The book analyzes the relationship between the U.S. doctrine of containment of communism and U.S. foreign policy in Vietnam. The book also examines the views of other participants in the conflict - including the government in Hanoi. It begins by describing the efforts of the Communist-led Vietminh Front to overthrow French rule in Vietnam and the U.S. reaction to those events. It then traces the gradual rise of U.S. involvement during the Truman, Eisenhower, Kennedy, and Johnson administrations, concluding with the introduction of U.S. combat troops in the summer of 1965. The book concludes with an overview of the U.S. experience in Vietnam and a discussion of whether there were feasible alternatives to the containment strategy that was pursed
Keywords: indochina,united states,vietnamese conflict; politics and government,foreign realtions,indochina; 1945,1961-1975; united states